2009
DOI: 10.1007/s11625-009-0090-4
|View full text |Cite
|
Sign up to set email alerts
|

Towards institutional analysis of sustainability science: a quantitative examination of the patterns of research collaboration

Abstract: This paper examines quantitatively the patterns of collaboration over geographical boundaries in the emerging field of sustainability science by empirically analyzing the bibliometric data of scientific articles. The results indicate that an increasing number of countries are engaged in research on sustainability, with the proportion of articles published through international collaboration rising as well. The number of countries engaged in international collaboration on sustainability research has been increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 18 publications
(16 reference statements)
6
56
1
1
Order By: Relevance
“…The reduction in the number of papers from Costa Rica in recent years may result from tightened standards in the journal and that space seem to be filling up with an increased presence of Brazilian articles in recent issues (JMN personal observation). Previous studies with other journals have reported that authors establish de facto networks that collaborate and repeatedly cite each other (Ronda & Guerras, 2010;Fatt, Abu Ujum & Ratnavelu, 2010;Schulz & Nicolai, 2015), and that neighboring countries share interests and collaborate in certain research topics (Yarime, Takeda & Kajikawa, 2010). Our results suggest that this shared interest research takes place in the cases of Mexico, Venezuela and Costa Rica, which are mostly covered by tropical ecosystems, share a common language (Spanish) and often collaborate in research (De Filippo, González, & Sanz-Casado, 2016).…”
Section: Discussionsupporting
confidence: 61%
“…The reduction in the number of papers from Costa Rica in recent years may result from tightened standards in the journal and that space seem to be filling up with an increased presence of Brazilian articles in recent issues (JMN personal observation). Previous studies with other journals have reported that authors establish de facto networks that collaborate and repeatedly cite each other (Ronda & Guerras, 2010;Fatt, Abu Ujum & Ratnavelu, 2010;Schulz & Nicolai, 2015), and that neighboring countries share interests and collaborate in certain research topics (Yarime, Takeda & Kajikawa, 2010). Our results suggest that this shared interest research takes place in the cases of Mexico, Venezuela and Costa Rica, which are mostly covered by tropical ecosystems, share a common language (Spanish) and often collaborate in research (De Filippo, González, & Sanz-Casado, 2016).…”
Section: Discussionsupporting
confidence: 61%
“…Key terms found across many themes include education, biotechnology, medical, lifestock, climate change, welfare and livelihoods (Kajikawa et al 2007). However, behind the diverse range of themes there is a pattern: the focused fields are significantly different between countries, and between the diverse networks of neighbouring country collaborators (Yarime et al 2010). Sustainability science provides information indispensible for solving the sustainability challenge.…”
Section: Sustainability Sciencementioning
confidence: 99%
“…Yarime, Takeda, and Kajikawa (2010) comment that various attempts have been initiated to create global systems of research collaboration among universities in order to improve the quality of studies. The country analysis seeks to identify the origins of the universities affiliated with the published authors.…”
Section: Data Collectionmentioning
confidence: 99%
“…According to Machado, Manfrin, Lima, Silva, and Maciel (2012), a country analysis consists of identifying the geographic locations of the universities through the author affiliations. Yarime et al (2010) note that an analysis of countries includes international collaborations within a specific thematic, which can be effective for sharing existing regional knowledge.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation